2003
DOI: 10.1097/01.brs.0000092386.96824.db
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Ablation of Osteoid Osteoma of the Spine

Abstract: Minimally invasive surgery can successfully be applied in the treatment of osteoid osteoma of the lumbar spine. When the nidus is not adjacent to the neural elements radiofrequency thermal ablation can be an effective and safe treatment of osteoid osteoma in the spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…In the literature, the heat dosage applied to the apex of the cauterization needle for the treatment of localized OO throughout is 4 min at 90°C [11,15] or 6 min at 90°C [9,17], with a success rate of approximately 90%.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the heat dosage applied to the apex of the cauterization needle for the treatment of localized OO throughout is 4 min at 90°C [11,15] or 6 min at 90°C [9,17], with a success rate of approximately 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several authors are sceptical regarding RFA for spinal osteoid osteomas because of the potential neurologic risks [9,12,14,19,21] and therefore open resection is still the treatment of choice for lesions of the occipitocervical junction [3]. Nevertheless, radiofrequency ablation of a spinal osteoid osteoma has been primarily reported in 1998 [18] and in recent years several authors reported their experience [6,7,12,14,21,23]. Animal models of RFA have shown that it may be performed safely in the vertebral body but the temperature of the surrounding soft tissue depends on the thickness of the cortical bone lamella [1,7].…”
Section: Discussionmentioning
confidence: 99%
“…They mainly affect long bones of children and of young adults and occur in the spine with a frequency of about 10% [11]. Traditional therapy of spinal lesions consists of open intralesional resection but recent papers report the use of CT-guided radiofrequency ablation (RFA) [6,7,12,14,18,21,23]. Nevertheless, RFA in the spine is limited due to the possible thermal damage of neural structures while it is the treatment of choice for osteoid osteomas of the extremities.…”
Section: Introductionmentioning
confidence: 99%
“…Osti and Sebben reported on the first case of lumbar osteoid osteoma of the spine treated successfully by radiofrequency coagulation [11]. Other reports were less enthusiastic about the use of this technique in vertebral osteoid osteomas adjacent to neural elements, because of the potential risk of neurologic complications [3,8,12,14]. In an ex-vivo study measuring temperature changes in the adjacent spinal canal while applying radiofrequency to vertebral bodies in pigs, Dupuy et al [4] stated that there was no cytotoxic temperature elevations recorded in the spinal canal.…”
Section: Discussionmentioning
confidence: 99%